2018
DOI: 10.1111/jce.13612
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs in acute new‐onset atrial fibrillation and their target mRNA network

Abstract: The miRNAs had different expression profiles dependent on the AF condition, with higher expression in the acute new-onset AF than well-controlled AF. Clinically, this may contribute to an effective assessment for patients, leading to early detection of AF and monitoring to reduce the risk of other serious cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
(54 reference statements)
0
17
0
2
Order By: Relevance
“…The associations of hsa-miR-133b and AF has been reported by several studies but different expression patterns were observed. da Silva et al found that hsa-miR-133b was up-regulated in acute new-onset AF patients with a 1.4-fold increased expression compared with well-controlled AF patients and control patients (da Silva et al, 2018). Li et al (2012) reported that miR-133 was down-regulated in chronic AF canines.…”
Section: Resultsmentioning
confidence: 99%
“…The associations of hsa-miR-133b and AF has been reported by several studies but different expression patterns were observed. da Silva et al found that hsa-miR-133b was up-regulated in acute new-onset AF patients with a 1.4-fold increased expression compared with well-controlled AF patients and control patients (da Silva et al, 2018). Li et al (2012) reported that miR-133 was down-regulated in chronic AF canines.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, only 40 studies fulfilled the eligibility criteria for meta-analysis after excluding duplicates, conference abstracts, reviews, letters, irrelevant studies, and studies that lacked important information. 3,510,26,28,29,3134,36,39,40,4466 Specific reasons for the exclusion of studies are listed in Supplementary Table 2. The list of the 40 studies characteristics is given in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…The tissue-related specificity exists in the miRNA expression, and miR-375 and miR-113b expression differed between blood samples 3,7,32 and tissue. 36,57 A total of 54 miRNAs were consistently differentially expressed in atrial tissue, among which increased miR-328 and decreased miR-1 were identified.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, this will reduce the level of protein encoded by the mRNA [14]. The regulation of miRNAs is highly complex, one miRNA can target multiple mRNAs simultaneously and one mRNA can be regulated by a variety of different miRNAs [15,16]. MiRNAs regulate gene expression in order to maintain their proper function and homeostasis.…”
Section: Types and Nomenclaturementioning
confidence: 99%